Understanding the implementation of the ethical code for the teacher profession in Cambodia - Pich Chueng; Sovann Ly (Journal of Professional Teacher Education, 2025)
This study examines the perceptions and implementation of the teacher professional ethics (TPE) code within the Cambodian education system. The TPE code is recognized as a crucial framework for enhancing teacher professionalism, integrity, identity, leadership, and educational practices; empirical evidence regarding its perception and implementation remains limited. Therefore, this study aims to explore participants’ understanding of TPE code; identify perceived barriers to its effective implementation; assess its implementation effectiveness; and propose constructive suggestions to address unethical practices. A qualitative research design was employed using in-depth interviews with 20 participants, consisting of one director, seven teacher trainers, and twelve teacher trainees at a teacher education institution in Cambodia. Data were analyzed thematically to identify key patterns and insights. The findings reveal that participants generally perceive TPE code as a set of rules, professional responsibilities, moral guidelines, and a tool for professional development and social recognition. However, its implementation is hindered by both internal factors (low motivation, limited understanding, economic pressures, and time constraints) and external factors (inadequate institutional support, social influences, and weak enforcement mechanisms). The implementation of TPE code is considered moderately effective, particularly in promoting ethical conduct, teaching practices, collaboration, and professional responsibilities. The study highlights the importance of continuous professional development, institutional support, effective leadership, and motivational strategies to strengthen ethical practices. It also recommends future research to expand methodological approaches and participant scope, as well as to explore the impact of leadership and institutional management on the successful implementation of teacher professional ethics.